2008
DOI: 10.1080/02841860701851871
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarrays compared with whole sections and biochemical analyses. A subgroup analysis of DBCG 82 b&c.

Abstract: (2008) Tissue microarrays compared with whole sections and biochemical analyses. A subgroup analysis of DBCG 82 b&c., Acta Oncologica, 47:4, 591-599,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 21 publications
1
53
1
Order By: Relevance
“…From the 532 FFPE samples with sufficient tumor tissue, RNA extraction were performed and expression of ESR1, PGR, ERBB2 and MKI67 were quantified with quantitative real time polymerase chain reaction (described in detail in Supplementary Material, available online at http://www.informahealthcare.com [13,[25][26][27]). If the quantification failed, data from medical records and immunohistochemistry (IHC) was used to determinate ER-, PR-and HER2-status.…”
Section: Methodsmentioning
confidence: 99%
“…From the 532 FFPE samples with sufficient tumor tissue, RNA extraction were performed and expression of ESR1, PGR, ERBB2 and MKI67 were quantified with quantitative real time polymerase chain reaction (described in detail in Supplementary Material, available online at http://www.informahealthcare.com [13,[25][26][27]). If the quantification failed, data from medical records and immunohistochemistry (IHC) was used to determinate ER-, PR-and HER2-status.…”
Section: Methodsmentioning
confidence: 99%
“…With multiplex cores, several reports have indicated that there is reasonable representation of tissue heterogeneity. 14,15 LeBaron et al 16 also have suggested a method for creating TAs without coring the blocks. With this method, the spot for each case is a tiny square; thus, the advantages of the Spiral Array technique described above cannot be achieved.…”
Section: Commentmentioning
confidence: 99%
“…Kidney tissue was placed in the first core of the upper left and right corner of the TMA block to ensure correct orientation when examining the slides. All analyses were performed with the use of TMAs, allowing semi-quantitative analysis [21,22].…”
Section: Preparation Of Tissue Microarraysmentioning
confidence: 99%
“…A suitable method for evaluation of marker proteins is immunohistochemistry (IHC) with the use of Tissue Micro Arrays (TMA). TMAs allow rapid, cost-effective and standardized analyses with the use of only a small amount of paraffin embedded tumor tissue and it has made immunohistochemical characterization of protein expression in large series of tumors easier and less laborious [21]. Furthermore, TMAs can be used for semi-quantitative analysis of various potential predictive marker proteins [22].…”
mentioning
confidence: 99%